Repositioning Legal Awareness Development Through Maqāṣid Al-Syarī‘Ah: A Value-Based Approach to Indonesia’s National Legal Culture - Amrizal Amrizal; Edy Saputra; Putri Alya Sabina; Hospi Burda (Prodi Hukum Ekonomi Syariah STAIN Teungku Dirundeng Meulaboh, 2026)
Legal awareness in Indonesia remains predominantly characterized by instrumental and sanction-driven compliance, despite high levels of religiosity, reflecting a structural weakness in national legal culture. This study aims to reposition legal awareness development by examining Maqāṣid al-Syarī‘ah as a value-based and ethical foundation capable of fostering internalized legal compliance within Indonesia’s national legal system. Employing a qualitative normative legal research design, this study analyzes classical Islamic legal thought—particularly Ibn ʿĀshūr’s formulation of maqāṣid—alongside contemporary legal scholarship and Indonesian legal discourse through thematic and comparative analysis. The findings demonstrate that prevailing positivist, socio-legal, and normative fiqh-oriented approaches remain limited in cultivating internal legal awareness, as they prioritize formal compliance, coercive enforcement, and doctrinal rigidity while neglecting ethical internalization and cultural resonance. In contrast, Maqāṣid al-Syarī‘ah provides an integrative ethical framework that aligns legal norms with moral objectives, public welfare (maṣlaḥah), and social meaning, thereby strengthening internalized legal compliance. This study further shows that although maqāṣid-based principles have been applied in various legal sectors in Indonesia, they remain fragmented and disconnected from legal awareness policy. The novelty of this study lies in its conceptual repositioning of Maqāṣid al-Syarī‘ah not merely as a normative fiqh doctrine or sectoral reform tool, but as a comprehensive ethical and cultural framework for legal awareness development within Indonesia’s national legal culture.